Perancangan Sistem Informasi Akuntansi Siklus Pembelian Toko Sumber Meubel Elektronik - Prayanthi, Ika; Rantung, Danny (Universitas Klabat, 2024)
Abstrak This community service activity aims to design a purchasing cycle accounting information system for Electronic Furniture Source Stores. This community service activity is a community activity that involves students of the Accounting Information System class as an output of implementing the knowledge gained in class, namely the Accounting Information System class project in MSMEs around the Universitas Klabat. The design of this accounting information system includes the creation of purchase accounting cycle procedures, document flowcharts, business document designs, and the implementation of purchase transaction simulations using Odoo Software.